Aspartate‐phobia of thermophiles as a reaction to deleterious chemical transformations. (17th November 2021) - Villain, Etienne; Fort, Philippe; Kajava, Andrey V
Abstract: Prokaryotes growing at high temperatures have a high proportion of charged residues in their proteins to stabilize their 3D structure. By mining 175 disparate bacterial and archaeal proteomes we found that, against the general trend for charged residues, the frequency of aspartic acid residues decreases strongly as natural growth temperature increases. In search of the explanation, we hypothesized that the reason for such unusual correlation is the deleterious consequences of spontaneous chemical transformations of aspartate at high temperatures. Our subsequent statistical analysis supported this hypothesis. This finding reveals that organisms have likely adapted to high temperatures by minimizing the harmful consequences of spontaneous chemical transformations. Abstract : We found that prokaryotes growing at high temperatures have a low proportion of aspartic acid residues in their proteins. This aspartate‐phobia of thermophiles can be explained by an adaptive mechanism used to minimize the harmful consequences of spontaneous chemical transformations of aspartate at high temperatures.